IN ON THE GRIFT: HOW PLATFORMS GOVERN AUTHENTICITY FOR NEO-COLONIAL ENDS - Graham, Timothy; Whelan-Shamy, Daniel (AoIR Selected Papers of Internet Research, 2023)
Cryptocurrency has attracted widespread criticism for its exploitative logics that consume resources and trap unwitting investors into highly volatile, unregulated markets with worsening wealth inequality. A key factor in the rise of crypto trading is social media, where an ecosystem of spammers, grifters, ‘crypto influencers’ and celebrities such as Elon Musk amplify hype and generate public interest. While platforms moderate orchestrated platform manipulation through the opaque concept of ‘coordinated inauthentic behaviour’ (CIB), here we argue that Twitter is largely ignoring widespread crypto-related CIB on its platform– because it is profitable. Informed by a study of 1.8 million tweets about the top five crypto coins, we develop a neocolonial perspective of CIB that highlights how Twitter exploits it strategically to turn a blind eye to financial exploitation and techno-utopian subjugation on the platform. While the line between authentic and inauthentic coordinated activity is not always clear cut, we suggest that platforms construct the problem in such a way that strategically obfuscates its distinction. This raises critical questions for content moderation and platform regulation that will require us to think outside the compromised nomenclature that platforms have invented for their own ends.